Genetic factors and not genetic on variation in milk production of a dual purpose cattle (Gaceta de Ciencias Veterinarias, 2019)
ABSTRACTObtaining cattle that express adaptability and efficient production in tropical environments is the objective in dual-purpose livestock research. In order to evaluate the genetic and non-genetic effects that affect the variation in milk production in dual-purpose cows, 3722 lactation records adjusted to 244 days (P244) of 1334 cows, belonging to a farm located in the municipality of La Ceiba, Trujillo State were analyzed. Model I, allowed to evaluate the non-genetic and genetic effects that affect the variation of P244, establishing as fixed effects: month of calving (MP), year of calving (AP), age at calving (EP), number of calving (NP), and racial group (GR), and as random effects: father, mother of the cow, and residual, being evaluated through an analysis of variance using mixed models methodology of the statistical package SAS®. Model II determined the components of (co) variances, genetic and non-genetic parameters, using a univariate animal model with the set of MTDFREML programs. Considering as fixed effects, those that were significant (P
Keywords: Livestock dual purpose; milk production; genetic effects; genetic parameters; inheritance index